Highlighting the Invisible: An Interview with Avan Sdiq. (11th November 2022) - Sdiq, Avan; Abdullah, Meriwan; Appelfeller, Allison
Abstract : Sulaimani-based artist Avan Sdiq talks about her involvement with Nawi Min Nawi Daikama, an activist project working to change the laws regarding the carti nishtinmani Iraqi (Iraqi identification card) for cases of children who are born after rape, abuse, or abandonment. Sdiq discusses what she thinks are the biggest challenges facing the art world in Kurdistan and her view of the role of the artist in Kurdish society.